A gelatin matrix-thrombin tissue sealant (FloSeal®) application in the management of groin breakdown after inguinal lymphadenectomy for vulvar cancer. Issue 4 (1st June 2004) - Han, L. Y.; Schimp, V.; Oh, J. C.; Ramirez, P. T.
Abstract : The rate of groin breakdown after radical wide vulvar excision and inguinal lymphadenectomy for vulvar cancer remains significant despite conservative surgical approaches. An 86-year-old Latin American woman underwent wide radical excision and bilateral inguinal lymphadenectomy for vulvar cancer. The postoperative course was complicated by bilateral groin wound separation and high output lymphorrhea. The patient responded to the application of a gelatin matrix-thrombin tissue sealant (FloSeal®) to the bases of each groin with resolution in lymphorrhea and formation of granulation tissue. The application of a gelatin matrix-thrombin tissue sealant (FloSeal®) may be a viable treatment in the management of groin breakdown in selected patients when conventional therapy produces suboptimal results.